2021
DOI: 10.3389/fonc.2021.641887
|View full text |Cite
|
Sign up to set email alerts
|

Transvesical Versus Posterior Approach to Retzius-Sparing Robot-Assisted Radical Prostatectomy: A Retrospective Comparison With a 12-Month Follow-Up

Abstract: ObjectivesTo assess the perioperative, functional, and oncological outcomes of transvesical robot-assisted radical prostatectomy (T-RARP) and posterior robot-assisted radical prostatectomy (P-RARP) for localized prostate cancer.Materials and MethodsWe analyzed the data of 96 patients who underwent T-RARP or P-RARP for localized prostate cancer between January 2017 and June 2019 in a retrospective fashion.ResultsNo significant differences in the baseline characteristics existed between the T-RARP and P-RARP arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Several pathophysiological factors may account for the occurrence of post-prostatectomy incontinence (PPI). Apart from the preoperative variables encompassing age at the time of operation, preexisting lower urinary tract symptoms, higher BMI, and bladder dysfunction, the structural damage to anatomic supporting structures and neural elements during the RP process may play a crucial part in the development of PPI ( 13 , 33 ). Given the comparability of all the preoperative variables between the two arms in our analysis, the significant differences in UC and EF recovery observed between the RARP and LRP groups in our study could be attributed to the benefits of robotic platforms in preserving membranous urethral and nerve components and allowing the reconstruction of the surrounding supporting structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several pathophysiological factors may account for the occurrence of post-prostatectomy incontinence (PPI). Apart from the preoperative variables encompassing age at the time of operation, preexisting lower urinary tract symptoms, higher BMI, and bladder dysfunction, the structural damage to anatomic supporting structures and neural elements during the RP process may play a crucial part in the development of PPI ( 13 , 33 ). Given the comparability of all the preoperative variables between the two arms in our analysis, the significant differences in UC and EF recovery observed between the RARP and LRP groups in our study could be attributed to the benefits of robotic platforms in preserving membranous urethral and nerve components and allowing the reconstruction of the surrounding supporting structures.…”
Section: Discussionmentioning
confidence: 99%
“…Larger PVs are also correlated with lower risks of PSMs and extracapsular invasion, as well as favorable pathologic characteristics, all of which contribute to favorable oncologic outcomes (9,31). Moreover, the distances between the risks of PSMs and occurrences of robust clinical events were relatively remote, greatly depending upon preoperative elements such as the preoperative PSA, advanced clinical stage, and higher Gleason scores (13,24). Indeed, we found relatively low BCR rates in the RARP group (7.9%) at a median follow-up time of 36.8 months and in the LRP group (8.6%) at a median follow-up of 32.8 months, which was consistent with the low BCR rates (10.5%) following RP for PCa with a large PV (≥50 ml) at a median followup period of 36.1 months in the study reported by Mandel et al (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Retzius-sparing/posterior approach to RARP, a technique preserving related anatomical structures in Retzius space [ 8 ], exhibits improved short-term continence rate. However, urologists were slow to adopt the posterior approach because of the steep learning curve and specific comments regarding the uncertainties of increased positive surgical margin (PSM) [ 9 ]. Recently, our team first conducted the transvesical approach to RARP, another procedure that avoids entry to the Retzius space, in patients afflicted with localized prostate cancer (PCa) [ 9 11 ], thus promoting early UC recovery.…”
Section: Introductionmentioning
confidence: 99%
“…However, urologists were slow to adopt the posterior approach because of the steep learning curve and specific comments regarding the uncertainties of increased positive surgical margin (PSM) [ 9 ]. Recently, our team first conducted the transvesical approach to RARP, another procedure that avoids entry to the Retzius space, in patients afflicted with localized prostate cancer (PCa) [ 9 11 ], thus promoting early UC recovery. Based on the outcomes of transvesical RARP for localized PCa [ 9 11 ], the transvesical approach could serve as a valid alternative to RARP in selected patients, providing promising postoperative UC with compromising oncologic control for localized PCa.…”
Section: Introductionmentioning
confidence: 99%